THE EMBLEMATIC FOCUS OF IVAN FRANKO’S RECEPTION - Soletsky, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The forms of reception and semiotic presence of Ivan Franko in the Ukrainian cultural and axiological semiosis have been studied in the paper. He “functions” there as some “cultural universal” incorporated into structural forms of the national identity delineated profile. Besides, he is the part of the most frequently employed visualizations required for basing the eidos like “patriotism”, “national commitment”, “sovereignty”, “industri-ousness” etc. The structure and the form of Franko’s “presence” in the Ukrainian mass and intellectual discourse is distinctly emblematic. Ivan Franko as a text and Ivan Franko as a man are amenable to deconstruction and interpretation in various traditional and ancient emblematic concepts.